An ImageJ‐based tool for three‐dimensional registration between different types of microscopic images. (14th January 2023) - Koyama, Hiroshi; Kishi, Kanae; Mikoshiba, Seiya; Fujimori, Toshihiko
Abstract: Three‐dimensional (3D) registration (i.e., alignment) between two microscopic images is very helpful to study tissues that do not adhere to substrates, such as mouse embryos and organoids, which are often 3D rotated during imaging. However, there is no 3D registration tool easily accessible for experimental biologists. Here we developed an ImageJ‐based tool which allows for 3D registration accompanied with both quantitative evaluation of the accuracy and reconstruction of 3D rotated images. In this tool, several landmarks are manually provided in two images to be aligned, and 3D rotation is computed so that the distances between the paired landmarks from the two images are minimized. By simultaneously providing multiple points (e.g., all nuclei in the regions of interest) other than the landmarks in the two images, the correspondence of each point between the two images, i.e., to which nucleus in one image a certain nucleus in another image corresponds, is quantitatively explored. Furthermore, 3D rotation is applied to one of the two images, resulting in reconstruction of 3D rotated images. We demonstrated that this tool successfully achieved 3D registration and reconstruction of images in mouse pre‐ and post‐implantation embryos, where one image was obtained during live imaging and another image was obtained from fixed embryos after live imaging. This approach provides a versatile tool applicable for various tissues and species. Abstract : We propose a user‐friendly image processing method by which we can three‐dimensionally align two images with multiple z ‐slices. This method enables us to easily compare two tissues or embryos labeled by different markers under three‐dimensional situations.